The research of begin the Apache Giraph. Issue 1 (1st June 2022) - Shen, Haowei
Abstract: Apache Giraph is an open-source image processing framework built from Apache Hadoop. Apache Giraph is based on bulk synchronous parallel and Google's Pregel. It is suitable for running large-scale logical calculations, such as page ranking, shared links, personalized ranking, etc. Giraph focuses on social graph computing and is at the core of Facebook's open graph tool, handling trillions of connections between users and their behaviors in a few minutes. But because the time is limited, the work just has been done with Hadoop. This paper will be mainly talked about Hadoop and how the difficulty to be solved.